(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: The status of hemostatic parameters, are useful physiological markers of organ and tissue damage and dysfunction. This study investigated the effect of Piroxicam on some hemostatic parameters of albino Wistar rats. Twenty-four (24) female albino Wistar rats were used for this study, they were randomly divided into four (4) groups of six (6) rats each. Group A served as control, Group B and C were rats treated with 0.1 mg/kg and 0.2 mg/kg piroxicam while Group D served as 0.2 mg/kg piroxicam treated rats administered with Vitamin E. The experiment lasted for a period of 4 weeks, after which the rats were euthanized. Blood sample was collected for measurement of bleeding time, clotting time, fibrinogen level and platelets count. One-way ANOVA was used to compare, means and a p<0.05 was considered significant. Result: Data generated showed that Piroxicam significantly (p<0.05) decreased the clotting time, platelets count and fibrinogen level. Piroxicam also significantly (p<0.05) increased the bleeding time level of the rats. Co-administration of Vitamin E significantly (p<0.05) increased the bleeding time, it also significantly decreased the clotting time, fibrinogen level and platelets counts. Conclusion: This study therefore shows that Piroxicam impairs hemostasis while Vitamin E administration further enhances the activities of Piroxicam on hemostatic parameters.